2001
DOI: 10.1002/pdi.262
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory, multidisciplinary education in diabetes care. Can it meet the needs of primary care organisations?

Abstract: ObjectivesTo assess the effectiveness and feasibility of mandatory, multidisciplinary education, in the context of a primary care organisation service development programme for diabetes care. To identify any obstacles to change and to measure changes in knowledge, service organisation and attitudes after a university based course in diabetes care.The courseIt was mandated by the primary care group of Ladywood, Birmingham, UK, that one general practitioner and one nurse from each practice should attend a course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Usually the IPE programme/course was voluntary and the participants received either study credits and/or a certificate upon completion. One professional course was mandatory (Hearnshaw et al, 2001), and one course offered a financial grant for participation (Lennon-Dearing, Florence, Garrett, Click, & Abercrombie, 2008). The programmes were identical for all the participants from various professions, except for three IPE programmes organized partly in parallel sessions, with disciplinespecific contents (Coates et al, 2008;Kipp, Pimlott, & Satzinger, 2007;Shiyanbola et al, 2012).…”
Section: Ipe Settings and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually the IPE programme/course was voluntary and the participants received either study credits and/or a certificate upon completion. One professional course was mandatory (Hearnshaw et al, 2001), and one course offered a financial grant for participation (Lennon-Dearing, Florence, Garrett, Click, & Abercrombie, 2008). The programmes were identical for all the participants from various professions, except for three IPE programmes organized partly in parallel sessions, with disciplinespecific contents (Coates et al, 2008;Kipp, Pimlott, & Satzinger, 2007;Shiyanbola et al, 2012).…”
Section: Ipe Settings and Methodsmentioning
confidence: 99%
“…In one program, the students participated in a week-long experience of living with diabetes, involving "insulin" injections (saline) four times a day, and appropriate blood glucose monitoring (Pittenger et al, 2013). In addition, patient cases were studied through clinical visits or team placements (Coates et al, 2008;Kipp et al, 2007;Lennon-Dearing et al, 2008), through internet-based clinical scenarios (Ching et al, 2015;MacNeill et al, 2014;Parekh, Bush, Cook, & Grant, 2015;Pittenger et al, 2013), and through text-based case studies (Hearnshaw et al, 2001;Herring et al, 2013;MacNeill et al, 2014).…”
Section: Ipe Settings and Methodsmentioning
confidence: 99%
“…[15][16][17] In the wider speciality of diabetes, programmes of continuing medical education have been shown to effectively disseminate practice guidelines, increase knowledge of diabetes and improve attitudes towards diabetes and its care. [18][19][20][21] Idiculla and colleagues, however, have inferred that diabetes guidelines have very little effect on increasing the information provided on relevant medical problems. 7 New advances in communication technology such as smart cards and electronic data interchange (EDI) may circumvent some of the problems associated with traditional modes of communication.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent UK research report showed that practice nurses' knowledge score on diabetes increased from 66% preeducation to 86% post-education programme [12]. The previous reports that many patients do not usually get formal diabetes education or encouragement for diabetes self-care might be related to the practice nurses' insufficient diabetes knowledge [13,14]. Therefore, the present study aimed to compare the knowledge of practice nurses on principles and concepts of diabetes self-management education (DSME) before and after a DSME training workshop in a Caribbean Island.…”
Section: Introductionmentioning
confidence: 99%